2012
DOI: 10.1111/j.1469-8986.2012.01351.x
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical orthostatic pulse pressure confirms mothers' ratings of ADHD in preschoolers

Abstract: Subclinical levels of orthostatic hypotension (OH) have been linked to a variety of emotional and behavioral outcomes across the life span. These connections are not surprising, given the multitude of correlated conditions, including autonomic control, cardiovascular functioning, baroreceptor activity, and dopamine and serotonin. The current study assessed blood pressure regulation in healthy preschool children ages 3-5 (n = 61). The Conner's Parent Rating Scale Revised was used to assess indexes of attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The significantly higher prevalence of orthostatic intolerance symptoms of neurodevelopmental patients compared to controls provides direct empirical evidence for this suggestion within the literature (Perlmuter et al, 2013, Goodman, 2016). Moreover, our larger study used quantitative data from patients with diagnosed neurodevelopmental conditions, extending an association between orthostatic symptoms and ADHD questionnaire score in fewer healthy individuals (Casavant et al, 2012) as opposed to confirmed diagnosis. We observed increased orthostatic intolerance across patients with autism, ADHD, and Tourette Syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The significantly higher prevalence of orthostatic intolerance symptoms of neurodevelopmental patients compared to controls provides direct empirical evidence for this suggestion within the literature (Perlmuter et al, 2013, Goodman, 2016). Moreover, our larger study used quantitative data from patients with diagnosed neurodevelopmental conditions, extending an association between orthostatic symptoms and ADHD questionnaire score in fewer healthy individuals (Casavant et al, 2012) as opposed to confirmed diagnosis. We observed increased orthostatic intolerance across patients with autism, ADHD, and Tourette Syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a more direct association is proposed between orthostatic hypotension and specific behavioural and emotional disorders (Perlmuter et al (2013). Correspondingly, in healthy preschool children, poorer pulse pressure regulation during orthostatic challenge (a measure of orthostatic hypotension) predicts higher ADHD scores (Casavant et al (2012). Moreover, children with poorer responses to orthostatic stress were more likely to be viewed as oppositional or have attention difficulties (Casavant et al (2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention-deficit hyperactive disorder, presenting with impulsive behavior, lack of concentration, and extreme hyperactivity, was recently shown to be associated with a poorer SBP regulation in a nonclinical sample. 71 In another study with a nonclinical sample, increased hopelessness was related to subclinical levels of change in SBP in response to an orthostatic challenge. 72 In at least one study, birth weight was shown to predict subclinical OH.…”
Section: Oh and Affective Disordersmentioning
confidence: 97%
“…2, 159-166, http://dx.doi.org/10.1080/17450128.2013 relationships have been observed in children, where poor orthostatic BP regulation has been associated with depressive symptoms (Stress, Mayefsky, & Perlmuter, 2003). Furthermore, poorer orthostatic BP regulation has been linked to greater risk of poorer cognitive performance (Casavant, Spivak, Wiltse, Chilamkurti, & Perlmuter, 2010), as well as inattention and oppositional behaviors (Casavant, Chae, Sherwani, & Perlmuter, 2012).…”
mentioning
confidence: 96%